Pengembangan Kepribadian Pemuda pada Era Society 5.0 untuk Menguatkan Konsep Diri - Yan Imam Santoso; Utomo Utomo; Rachmat Imam Muslim; Retna Widyastuti; Mufdi Yukanto (Universitas Muhammadiyah Manado, 2025)
Rapid technological developments in the Society 5.0 era have had a significant impact on the character and personality of the younger generation. Ease of access to information and interaction in cyberspace has the potential to cause the younger generation to lose their identity and fall into negative behavior. Strengthening self-concept is crucial in facing this challenge. This research aims to strengthen students' self-concept as an effort to develop personality and build positive character in the Society 5.0 era. This research involved 50 students from various organizations at Muhammadiyah University Kendal Batang. The method used is a socialization workshop with a self-project approach, where students are asked to make a wish list and determine their priority scale. Evaluation is carried out through surveys to measure understanding of self-concept before and after the activity. The survey results showed an increase in students' understanding of self-concept after participating in the activity. Students become better able to recognize themselves, determine goals, and develop plans to achieve their goals. Apart from that, this activity also increases students' self-confidence and motivation. Strengthening self-concept through socialization workshop activities has proven effective in developing student personalities in the Society 5.0 era. Strengthening self-concept helps students build positive character, increase self-confidence, and develop the ability to determine life goals and develop plans to achieve them.